Effect of Rice Bran Oil Spread (RBOS) as a fat substitute on the sensory properties of baked products: EFFECT OF RICE BRAN OIL SPREAD ON SENSORY PROPERTIES OF BAKED PRODUCTS - RIZWANA SHAIK; APARNA KUNA; MOHIBBE AZAM; MANORAMA KANURI (Journal of Oilseeds Research, 2018)
Studies were carried out to replace Hydrogenated Fat (HF) with Rice Bran Oil (RBO) and two varieties of Rice Bran Oil Spread - RBOS1 and RBOS2 in the preparation of cake, cookies, piecrusts, muffins and doughnuts. Sensory evaluation of all the baked products prepared with HF, RBO, RBOS1 and RBOS2 was carried out using a 9 point hedonic score card and results indicated that cakes were most liked followed by piecrust and muffins prepared with RBOS2. There was no significant difference in overall acceptability of baked products made with HF and RBOS2 indicating that RBOS2 can be used for development of baked products without any compromise on the sensory attributes. All baked products made with RBOS2 were well accepted by the respondents compared to HF indicating that RBOS2 can be popularized as a baking fat.